2019
DOI: 10.1002/cam4.2448
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of SP1/Syncytin1 axis inhibits the proliferation and metastasis through the AKT and ERK1/2 signaling pathways in non‐small cell lung cancer

Abstract: Syncytin 1 is considered as an oncogene in various malignant tumors, but its effect on non‐small cell lung cancer (NSCLC) has not been reported. We investigated the specific role of Syncytin 1 on NSCLC through the transfection of Syncytin 1 knockdown or overexpression plamids in A549 cells. Our results proved that knockdown of Syncytin 1 inhibited the proliferation, and blocked the cell cycle on G1 phase by inhibiting the expression of Nusap1, Cyclin D1, CDK6, and CDK4. Cell cycle arrest also leaded to increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 36 publications
4
12
0
Order By: Relevance
“…SP1 was reported to be expressed at high levels in NSCLC and involved in NSCLC progression by regulating multiple aggressive behaviors. [28][29][30] Our rescue experiments further demonstrated that the miR-324-5p inhibition or SP1 overexpression partially reversed the tumorinhibiting impacts of LINC00491 knockdown in NSCLC cells. These results suggested that the miR-324-5p/SP1 axis was required for LINC00491-triggered regulatory mechanism in the malignancy of NSCLC.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…SP1 was reported to be expressed at high levels in NSCLC and involved in NSCLC progression by regulating multiple aggressive behaviors. [28][29][30] Our rescue experiments further demonstrated that the miR-324-5p inhibition or SP1 overexpression partially reversed the tumorinhibiting impacts of LINC00491 knockdown in NSCLC cells. These results suggested that the miR-324-5p/SP1 axis was required for LINC00491-triggered regulatory mechanism in the malignancy of NSCLC.…”
Section: Discussionsupporting
confidence: 53%
“…Among them, SP1 (Figure 4A) was chosen for further corroboration due to its wellcharacterized pro-oncogenic roles during NSCLC progression. [28][29][30] Luciferase reporter assay was employed to verify the predicted results. The results revealed that ectopic miR-324-5p expression reduced the luciferase activity driven by the SP1-WT in H522 and SK-MES-1 cells, while it did not affect the luciferase activity of SP1-MUT (Figure 4B).…”
Section: Sp1 Is a Direct Target Of Mir-324-5p In Nsclc Cells And Is Under The Control Of Linc00491 Via Sponging Mir-324-5pmentioning
confidence: 99%
“…They also might constitute spliceosome to abnormally participate in the splicing of mRNA, regulation of genes expression, causing abnormalities in protein synthesis. Other examples were the binding of miRNA or piRNA to cause the degradation of relevant RNA and result in functional disorder of their target molecules downstream of the ncRNA (Viswanathan, Daley & Gregory, 2008;Dong et al, 2019;Li et al, 2019d). They could also bind the mRNA or ribonucleoproteins to block or promote the translation of proteins (Seetharaman et al, 2016;Fei et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In non-small cell lung cancer, the inhibited expression of NUSAP1 could result in the blocking the cell cycle on G1 phase. 28 . In addition, NUSAP1 Inhibited Cell Proliferation in Invasive Breast Cancer Cells.…”
Section: Overexpression Of Bub1b Cdk1 Ccna2mentioning
confidence: 99%